Effectivity of Artery Ligation for Bleeding Control in Placenta Accreta Spectrum: A Systematic Review - Daniati, Lidya; Rahardjo, Bambang (Jurnal Kedokteran Brawijaya, 2026)
Placenta accreta spectrum (PAS) is a potentially life-threatening obstetric condition that causes severe postpartum hemorrhage. This study aimed to evaluate these techniques and their effectiveness in controlling postpartum hemorrhage. This systematic review used four databases: ScienceDirect, PubMed, Embase, and Scopus. We included studies on arterial ligation or occlusion, particularly of the internal iliac, uterine, hypogastric, or abdominal arteries, that compared arterial occlusion with conservative therapy or other interventions in women with PAS. We included eighteen studies with 1,338 patients. A total of 884 patients underwent the arterial ligation technique, whereas 454 underwent the balloon technique. Several studies have shown that arterial ligation or ballooning may be beneficial in controlling bleeding and reducing the need for hysterectomy. In contrast, other studies found that arterial ligation and occlusion did not result in significant differences in terms of intraoperative blood loss, required hysterectomy, and blood transfusion. All studies consistently found that arterial ligation and occlusion led to an increase in overall operative time compared to the control group. In addition, arterial ligation and occlusion are considered safe techniques with few complications. Arterial ligation and occlusion are effective techniques for managing PAS, particularly for controlling blood loss. Arterial ligation and occlusion are safe procedures with minimal complications.